6. Q6c
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p>Factor, if possible.</p><p><code class='latex inline'>4k^2+15k+9</code></p>
Similar Question 2
<p>Factor.</p><p><code class='latex inline'>\displaystyle 4 q^{2}-8 q-5 </code></p>
Similar Question 3
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>15x^2+7x-2</code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Factor, if possibsle.</p><p><code class='latex inline'>\displaystyle 4 r^{2}+12 r+3 </code></p>
<p>Factor.</p><p><code class='latex inline'>32b^2+40b-12</code></p>
<p>Factor. </p><p> <code class='latex inline'>6n^2+26n-20</code></p>
<p>Factor. </p><p><code class='latex inline'>\displaystyle 2 m^{2}-9 m+4 </code></p>
<p>Factor each expression.</p><p><code class='latex inline'>\displaystyle 4 x^{2}-4 x+1 </code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 3 m^{2}+5 m-2 </code></p>
<p>Factor.</p><p><code class='latex inline'>4w^2+8w-21</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 12+18 t+8 t^{2}</code></p>
<p>Factor each expression.</p><p><code class='latex inline'>5b^3-17b^2+6b</code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>6x^2-x-15</code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>15x^2+7x-2</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 8 x^{2}+24 x+18 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 2 x^{2}-7 x+5 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>2k^2-13k+21</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 4 t^{2}+8 t+3 </code></p>
<p>Factor.</p><p><code class='latex inline'>30z^2-34z-8</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>3d^2+17d+10</code></p>
<p>Factor. </p><p><code class='latex inline'> \displaystyle 6a^2 - 23a + 15 </code></p>
<p>Factor.</p><p> <code class='latex inline'>63n^2+126n+48</code></p>
<p>Factor.</p><p><code class='latex inline'>5d^2+8-14d</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 2-7 m+3 m^{2}</code></p>
<p>Factor. </p><p><code class='latex inline'>15x^2-4x-4</code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 8 z^{2}+10 z+3 </code></p>
<p>Factor, if possibsle.</p><p><code class='latex inline'>\displaystyle 5 t^{2}+7 t+2 </code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 2x^2 -7x - 15 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 12 y^{2}-11 y+2</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 5 m^{2}-11 m+2 </code></p>
<p>Factor. </p><p><code class='latex inline'>24y^2-10y-25</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 6ax^2+5ax-4a </code></p>
<p>Factor each expression.</p><p><code class='latex inline'>-7a^2-29a+30</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 7x^2-19x -6 </code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 6 x^{2}+19 x+15 </code></p>
<p>Determine the greatest common factor of each expression.</p><p><code class='latex inline'>7x^2+14x-21</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>5b^2-13b+6</code></p>
<p>Factor. </p><p><code class='latex inline'>8k^2+43k+15</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 15 n^{2}-n-2 </code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 4b^2 - 5b + 1 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 3 x^{2}+x-4 </code></p>
<p>Factor. Then, substitute <code class='latex inline'>x=2</code> into both forms. Are the results the same? Explain. </p><p> <code class='latex inline'>7x^2-23x+6</code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 9d^2 -6d + 1 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6 m^{2}-13 m+6 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 3 t^{2}-10 t+8 </code></p>
<p>Factor.</p><p><code class='latex inline'>6j^2+3j-45</code></p>
<p>How would you decompose the x—term to factor each polynomial?</p><p><code class='latex inline'>\displaystyle 30 x^{2}-9 x-3 </code></p>
<p>Factor each expression completely. <code class='latex inline'>\displaystyle (x-2)^{2}-15(x-2)+56 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'> \displaystyle 25x^2 + 30x + 4 </code></p>
<p>Factor fully</p><p><code class='latex inline'>\displaystyle 7x^2-26x -8 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>12h^2-28h+15</code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 9x^2 - 42x + 49 </code></p>
<p>Factor, if possibsle.</p><p><code class='latex inline'>\displaystyle 2 x^{2}+11 x+14 </code></p>
<p>Factor. </p><p><code class='latex inline'> \displaystyle 6y^2 + 29y + 9 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>6m^2-8m+4</code></p>
<p>Factor. </p><p> <code class='latex inline'>2a^2-11a+12</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6 y^{2}+y-1 </code></p>
<p>Factor. </p><p> <code class='latex inline'>6x^2-x-12</code></p>
<p>Factor. </p><p><code class='latex inline'>30r^2-85r-70</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 18 y^{2}+60 y+50 </code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 6x^2 - x - 2 </code></p>
<p>Factor.</p><p> <code class='latex inline'>24d^2+35-62d</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 3 t^{2}+4 t-20 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>5h^2-14h-3</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>4k^2+15k+9</code></p>
<p>Fully factor each polynomial by applying one or more strategies.</p><p><code class='latex inline'>\displaystyle 6 z^{2}+z-1 </code></p>
<p>Factor each expression. Remember to divide out all common factors first.</p><p><code class='latex inline'>\displaystyle 18 x^{2}+15 x-3 </code></p>
<p>Fully factor each polynomial by applying one or more strategies.</p><p><code class='latex inline'>\displaystyle 4 n^{2}+10 n-6 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 10 t^{2}+11 t-6 </code></p>
<p>Factor, if possible.</p><p> <code class='latex inline'>9b^2-24b+7</code></p>
<p>Factor.</p><p><code class='latex inline'>10a^2+a - 3</code></p>
<p>Factor each expression.</p><p><code class='latex inline'>18v^2+33v-30</code></p>
<p>Factor. </p><p><code class='latex inline'>8x^2+10x+3</code></p>
<p>Factor each polynomial.</p><p><code class='latex inline'>\displaystyle 12 x^{2}-18 x-24 </code></p>
<p>Factor each expression completely.</p><p><code class='latex inline'>\displaystyle 12 x^{2}+36 x+27 </code></p>
<p>Factor.</p><p> <code class='latex inline'>6n^2-20+26n</code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 12m^2 + 20m - 8 </code></p>
<p>Factor each, if possible.</p> <ul> <li><code class='latex inline'> 2x^2 - x -6 </code></li> </ul>
<p>Factor, if possible.</p><p><code class='latex inline'>4x^2+26x+9</code></p>
<p>Factor each expression. <code class='latex inline'>\displaystyle 5 t^{2}+28 t+32 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>12g^2-7g-10</code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>4x^2-16x+15</code></p>
<p>Factor.</p><p> <code class='latex inline'>18m^2-3m-10</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 18 s^{2}-7 s-1</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 9 t^{2}+3 t-6 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 4 y^{2}-11 y+9 </code></p>
<p>Factor.</p><p><code class='latex inline'>15x^2+4x-4</code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 9g^2 + 4g - 10 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>6v^2-v-15</code></p>
<p>Factor, if possibsle.</p><p><code class='latex inline'>\displaystyle 3 m^{2}+10 m+3 </code></p>
<p>Factor.</p><p><code class='latex inline'>8x^2+18x+7</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 5 t^{2}+2 t-2 </code></p>
<p>Factor each expression.</p><p><code class='latex inline'>48c^2-160c+100</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6+5 y-6 y^{2} </code></p>
<p>Factor each expression completely.</p><p><code class='latex inline'>\displaystyle 2 a^{2}-16 a+32 </code></p>
<p>Factor. Then, substitute <code class='latex inline'>x=2</code> into both forms. Are the results the same? Explain. </p><p><code class='latex inline'>15x^2-2x-8</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 9w^2-24w + 7 </code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 4 c^{2}-14 c-8 </code></p>
<p>Factor each expression.</p><p> <code class='latex inline'>6x^2+34x-12</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 2 y^{2}+11 y+15</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 36a^2+12a + 1 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6 x^{2}-5 x-4 </code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>2x^2-5x-3</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 12 r^{2}+27 r+15</code></p>
<p>Factor. </p><p><code class='latex inline'>16x^2+4x-6</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 2 m^{2}+2 m-3 </code></p>
<p>Factor, if possibsle.</p><p><code class='latex inline'>\displaystyle 3 x^{2}-5 x+2 </code></p>
<p>Factor. </p><p><code class='latex inline'>\displaystyle 6 x^{2}-x-2 </code></p>
<p>Factor each expression. <code class='latex inline'>\displaystyle 3 x^{2}+7 x-20 </code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>2x^2+x-3</code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 4a^2 -20a + 25 </code></p>
<p> Factor <code class='latex inline'>5x^2+11x+2</code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>6x^2+17x+5</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 8y^2 + 19y + 6 </code></p>
<p>Factor.</p><p><code class='latex inline'>18x^2+60x+50</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>5u^2+7u-3</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 5 y^{2}-14 y-3 </code></p>
<p>Fully factor each polynomial by applying one or more strategies.</p><p><code class='latex inline'>\displaystyle 8 u^{2}-2 u-6 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>8k^2-2k-3</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 2 x^{2}-2 x-6 </code></p>
<p>Factor by grouping.</p><p><code class='latex inline'> \displaystyle 8m^2 - 16m + 4 </code></p>
<p>Factor.</p><p> <code class='latex inline'>10x^2+3x-1</code></p>
<p>Factor each, if possible.</p> <ul> <li><code class='latex inline'> 10x^2 + 11x - 6 </code></li> </ul>
<p>Factor, if possible.</p><p><code class='latex inline'>3y^2+4y-7</code></p>
<p>Factor.</p><p><code class='latex inline'>35x^2-27x-18</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>12s^2+31s+20</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>5m^2+14m+8</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 4 x^{2}+6 x+2 </code></p>
<p>Factor.</p><p><code class='latex inline'>6c^2-13c+5</code></p>
<p>Factor. You may first need to determine a common factor. </p><p><code class='latex inline'>2x^2-7x-4</code></p>
<p>Each of the following is not factorable over the integers. Why not?</p><p><code class='latex inline'>36a^2+107a+81</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>4m^2-m+7</code></p>
<p>Factor each expression completely.</p><p><code class='latex inline'>\displaystyle 3(2 a-3)^{2}+17(2 a-3)+10 </code></p>
<p>Factor fully.</p><p><code class='latex inline'>12x^2+4x-21</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 10 x^{2}-17 x+3 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6 r^{2}+15 r+9</code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle p^2 + 12p + 36 </code></p>
<p>Factor. </p><p><code class='latex inline'> \displaystyle 2x^2 + 7x + 6 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6 x^{2}+7 x+2 </code></p>
<p>Factor each expression.</p><p><code class='latex inline'>10a^2+3a-1</code></p>
<p>Factor completely if possible. If not possible, complete the square.</p><p><code class='latex inline'>\displaystyle 2x^2 + 4x + 1 </code></p>
<p>Factor each expression completely.</p><p><code class='latex inline'>\displaystyle 4 n^{2}-20 n+24 </code></p>
<p>Factor.</p><p> <code class='latex inline'>6x^2+7x-3</code></p>
<p>Determine two values of <code class='latex inline'>h</code> so that each trinomial can be factored over the integers.</p><p><code class='latex inline'>2x^2+hx+4</code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>10x^2+9x-9</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>12r^2-11r+2</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 4 x^{2}-18 x-10</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 6x^2 -x -2 </code></p>
<p>Factor each expression.</p><p> <code class='latex inline'>8x^2-13xy+5y^2</code></p>
<p>Factor each, if possible.</p> <ul> <li><code class='latex inline'> 8x^2 - 10x - 3 </code></li> </ul>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 2 x^{2}-5 x+3 </code></p>
<p>How would you decompose the x—term to factor each polynomial?</p><p><code class='latex inline'>\displaystyle 6 x^{2}+x-1 </code></p>
<p>Factor each expression. <code class='latex inline'>\displaystyle 7 x^{2}-8 x-12 </code></p>
<p>Factor.</p><p><code class='latex inline'>6p^2-19p-7</code></p>
<p>Factor. Then, substitute <code class='latex inline'>x=2</code> into both forms. Are the results the same? Explain. </p><p> <code class='latex inline'>4x^2+12x+5</code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 14k^2 -31k - 10 </code></p>
<p>Factor.</p><p><code class='latex inline'>15y^2+26y+8</code></p>
<p>Factor.</p><p><code class='latex inline'>6x^2-13x+6</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>4p^2+7p+8</code></p>
<p>Factor.</p><p><code class='latex inline'>8h^2-10h+3</code></p>
<p>Factor each polynomial.</p><p><code class='latex inline'>\displaystyle 9 x^{2}-3 x+18 </code></p>
<p>Factor.</p><p><code class='latex inline'>15x^2-53x +42</code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 7 s^{2}+16 s+4 </code></p>
<p>Factor.</p><p><code class='latex inline'> \displaystyle 2y^2+5y-7 </code></p>
<p>Factor.</p><p><code class='latex inline'>16a^2-50a+36</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6 x^{2}-x-1 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>10w^2+15w+3</code></p>
<p>Factor. </p><p><code class='latex inline'>6m^2-3m-3</code></p>
<p>How would you decompose the x—term to factor each polynomial?</p><p><code class='latex inline'>\displaystyle 7 x^{2}-50 x-48 </code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 4 q^{2}-8 q-5 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>6m^2-17m+5</code></p>
<p>Factor each expression. <code class='latex inline'>\displaystyle 3 x^{2}+31 x+36 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>16c^2+14c-15</code></p>
<p>Factor fully.</p><p><code class='latex inline'>\displaystyle 20 m^{2}-8 m-12 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 8 x^{2}-10 x-3 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>6y^2+19y+8</code></p>
<p>Factor each expression. <code class='latex inline'>\displaystyle 5 r^{2}+23 r+26 </code></p>
<p>Factor, if possible.</p><p> <code class='latex inline'>8k^2-6k-5</code></p>
<p>Factor each expression.</p><p><code class='latex inline'>6x^2+5x+1</code></p>
<p>Factor.</p><p><code class='latex inline'>10m^2+m-3</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6+5 y-4 y^{2}</code></p>
<p>Factor.</p><p><code class='latex inline'>4x^2-20x+25</code></p>
<p>Factor each expression.</p><p><code class='latex inline'>2c^2+5c-12</code></p>
<p>Factor each expression.</p><p><code class='latex inline'>2x^2+x-6</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 8y^{2}-22 y+12</code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 2 g^{2}-11 g+15 </code></p>
<p>Factor. </p><p><code class='latex inline'>\displaystyle 3 t^{2}+8 t+5 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 2 t^{2}+9 t-5 </code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>3x^2-x-10</code></p>
<p>Explain how to factor <code class='latex inline'>\displaystyle 3 x^{2}+6 x-72 </code> completely.</p>
<p>Factor, if possible.</p><p><code class='latex inline'>10a^2+9a-7</code></p>
<p>Factor.</p><p><code class='latex inline'>12v^2-8v-4</code></p>
<p>Factor, if possibsle.</p><p><code class='latex inline'>\displaystyle 6 x^{2}+11 x+3 </code></p>
<p>Factor.</p><p><code class='latex inline'>5a^2-13a-6</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 9 x^{2}-15 x-4 </code></p>
<p>Factor. You may first need to determine a common factor. </p><p><code class='latex inline'>2x^2+10x+8</code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>2x^2+7x+3</code></p>
<p>Factor. </p><p><code class='latex inline'>\displaystyle 4 y^{2}+4 y-3 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 6 x^{2}+x-4</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 2 x^{2}-x-6 </code></p>
<p>Factor each expression.</p><p> <code class='latex inline'>3n^2-11n-4</code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 5 m^{2}+17 m+6 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>\displaystyle 9 z^{2}-9 z+2 </code></p>
<p>Factor, if possible.</p><p><code class='latex inline'>9x^2-15x-4</code></p>
<p>Factor.</p><p> <code class='latex inline'>2a^2-11a+12</code></p>
<p>Factor each expression.</p><p><code class='latex inline'>4x^2-16x+15</code></p>
<p>Factor. You may first need to determine a common factor. </p><p> <code class='latex inline'>2x^2-15x+7</code></p>
<p>Factor. Then substitute x = 3 into both forms. Are the results the same? Explain.</p><p><code class='latex inline'>8x^2+10x-3</code></p>
<p>Factor.</p><p><code class='latex inline'>\displaystyle 5 h^{2}+4 h-12 </code></p>
<p>Factor, if possibsle.</p><p><code class='latex inline'>\displaystyle 2 y^{2}+9 y+9 </code></p>
<p>Factor each, if possible.</p> <ul> <li><code class='latex inline'> 9x^2 - 15x - 4 </code></li> </ul>
<p>How would you decompose the x—term to factor each polynomial?</p><p><code class='latex inline'>\displaystyle 12 x^{2}+9 x-30 </code></p>
<p>Factor. You may first need to determine a common factor. </p><p><code class='latex inline'>5x^2+17x+6</code></p>
How did you do?
I failed
I think I failed
I think I got it
I got it
Another question?
Found an error or missing video? We'll update it within the hour! 👉
Report it
Save videos to My Cheatsheet for later, for easy studying.